New Combinations for Burmese Bamboos - Naithani, H. B.; Rennet, S. S. R. (Indian Forester, 1991)
Consequent to the merger of Cephaioslochyum, Dendrochloa and Neahouzeaua with Schizostachyum and Klemachloa with Dendrocalamus seven new combination. Viz. Schizostachyum burmanicum (Parker&Parkinson) Naithani&Bennet. S. distans (Parkinson) Naithani&Bennet. S .scanden. (Bor) Naithani&Bennet, S. strictum (Parker) Naithani&Bennet, S. tavoyanum (Gamble) Naithanl&Bennet, S. virgatum (Munro) Naithani&Bennet and Dendrocalamus detinens (Parker) Naithanl&Bennet, have been made In this paper or Burmese species.